2015
DOI: 10.1111/jvim.13606
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Different Stages of Disease Severity in Dogs with Chronic Valvular Heart Disease

Abstract: BackgroundIn humans with heart disease, vitamin D deficiency is associated with disease progression and a poor prognosis. A recent study showed that serum 25‐hydroxyvitamin D [25(OH)D] concentration, the hallmark of vitamin D status, was lower in dogs with heart failure than in normal dogs, and a low concentration was associated with poor outcome in dogs with heart failure.ObjectivesTo elucidate the vitamin D status of dogs with chronic valvular heart disease (CVHD) at different stages of disease severity.Anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
2
22
0
1
Order By: Relevance
“…Decreased blood 25(OH)D concentrations also have been reported in dogs with several other diseases; however, a key limitation shared by many of these studies is that the study designs did not account for other factors that may influence blood 25(OH)D concentrations, such as dietary vitamin D intake. Importantly, little evidence‐based research exists as to which factors may influence blood 25(OH)D concentrations in the dog .…”
mentioning
confidence: 99%
“…Decreased blood 25(OH)D concentrations also have been reported in dogs with several other diseases; however, a key limitation shared by many of these studies is that the study designs did not account for other factors that may influence blood 25(OH)D concentrations, such as dietary vitamin D intake. Importantly, little evidence‐based research exists as to which factors may influence blood 25(OH)D concentrations in the dog .…”
mentioning
confidence: 99%
“…In a second study, an association between vitamin D and degree of cardiac remodelling was observed, in which concentrations of 25(OH)D were significantly lower in the B2 and C/D stages compared to the B1 stage of CHF (Osuga et al, 2015). Despite no difference was found in the daily intake of vitamin D between the groups, a laboratory evaluation of the vitamin D content in the foods was not performed and daily vitamin D intake was only estimated using the information given by the manufacturer or presented on labels, and information regarding the amount of food consumed and others diet history information provided by the owners through a questionnaire applied to them.…”
Section: Vitamin D and Congestive Heart Failurementioning
confidence: 88%
“…The relationship of vitamin D and diseases has also been investigated in dogs and cats, and some studies found association between low vitamin D status and some types of cancer (Selting, Sharp, Ringold, Thamm, & Backus, 2016;Wakshlag et al, 2011;Weidner et al, 2017), congestive heart failure (Kraus et al, 2014;Osuga et al, 2015), gastrointestinal diseases (Allenspach, Rizzo, Jergens, & Chang, 2017;Gow et al, 2011;Lalor et al, 2014;Titmarsh, Gow, Kilpatrick, Cartwright, et al, 2015;Titmarsh, Gow, Kilpatrick, Sinclair, et al, 2015), acute pancreatitis (Kim et al, 2017), acute polyradiculoneuritis (Laws, Kathrani, Harcourt-Brown, Granger, & Rose, 2018), chronic kidney disease (Cortadellas, Fernandez del Palacio, Talavera, & Bayón, 2010;Galler et al, 2012;Gerber, Hässig, & Reusch, 2003;Gerber, Hauser, & Reusch, 2004;Parker, Harjes, et al, 2017) and infectious diseases (Lalor et al, 2012;Rodriguez-Cortes et al, 2017;Rosa, Schoeman, Berry, Mellanby, & Dvir, 2013;. Although these studies do not prove a cause-effect relationship, they provide a basis for future studies to investigate possible positive effects of vitamin D supplementation on improving health status and reducing the risk of developing diseases.…”
Section: Introductionmentioning
confidence: 99%
“…2014 ). Another study demonstrated that median 25(OH)D concentrations were significantly lower in dogs with chronic valvular heart disease stage B2 and C/D disease than dogs with stage B1 disease (Osuga et al . 2015 ).…”
Section: Vitamin D and Cardiac Diseasesmentioning
confidence: 99%